Self-governance and social inclusion in a post-socialist city - Kumer, Peter (Teorija in praksa, 2020)
The tendency of artists and creative professionals, ranging from non-profit and for-profit firms, individual artists, and cultural participants, to cluster in a specific area is observed and discussed in a large body of literature. However, the ways these districts are internally organised has received much less attention. In Ljubljana, one can find five different arts districts that emerged via grass-roots and top-down planning approaches. The article explores their community through the concepts of self-governance, social inclusion, and the right to the city. Our examination of the collective activities in these districts shows that the naturally-occurring districts reflect a spatial political agenda. Those active in such areas are resistant to heteronomy, formal regulation and hierarchy while being engaged in activism, social justice advocacy and artistic self-expression. In contrast, a city designation allows less freedom in management and organisation of the space and does not conflict with authorities over control of the land. While both district types reveal a strong desire to constantly change and produce novelty, the naturally-occurring districts are evolving at a faster pace. The article highlights the value of self-organisation and informal networks in the construction and development of arts districts.
Keywords: kreativno soustvarjanje prostora; kulturne soseske; kulturni grozdi; občutenje prostora; utemeljevalna teorija